A study of myFTMSK web portal visitor behavior using visitor tacking system / Mohd Rosli Ab Sukor - Ab Sukor, Mohd Rosli (2005)
In summary, the objective of this thesis is to study about myFTMSK web portal visitor behavior based on the information that collected from visitor tracking system that can be applied into this web portal. The information about the visitor behavior that will study in project are divided into 4 categories first is visitor behavior based on incoming traffic, secondly based on referring and last based on the system environment that visitor use. . The information that produces is needed by the web master to study the behavior of the visitor. From the information that get, the system will generate the statistic to view the information